Mapping the interaction site and effect of the Siglec-9 inflammatory biomarker on human primary amine oxidase - Leonor Lopes de Carvalho; Heli Elovaara; Jerôme de Ruyck; Gerard Vergoten; Sirpa Jalkanen; Gabriela Guédez; Tiina A. Salminen (NATURE PUBLISHING GROUP, 2022)
Human primary amine oxidase (hAOC3), also known as vascular adhesion protein 1, mediates leukocyte rolling and trafficking to sites of inflammation by a multistep adhesion cascade. hAOC3 is absent on the endothelium of normal tissues and is kept upregulated during inflammatory conditions, which is an applicable advantage for imaging inflammatory diseases. Sialic acid binding immunoglobulin like-lectin 9 (Siglec-9) is a leukocyte ligand for hAOC3. The peptide (CARLSLSWRGLTLCPSK) based on the region of inflammation using Positron Emission Tomography (PET). In the present study, we show that the Siglec-9 peptide binds to hAOC3 and triggers its amine oxidase activity towards benzylamine. Furthermore, the hAOC3 inhibitors semicarbazide and imidazole reduce the binding of wild type and Arg/Ala mutated Siglec-9 peptides to hAOC3. Molecular docking of the Siglec-9 peptide is in accordance with the experimental results and predicts that the R3 residue in the peptide interacts in the catalytic site of hAOC3 when the topaquinone cofactor is in the non-catalytic on-copper conformation. The predicted binding mode of Siglec-9 peptide to hAOC3 is supported by the PET studies using rodent, rabbit and pig AOC3 proteins.